PERKAWINAN BEDA AGAMA DAN PLURALISME HUKUM DI INDONESIA - Nada Intan Soraya (2022)
Interfaith marriages have become a controversial issue in Indonesia. The doubts of interfaith couples to continue their relationship to a more serious level, namely marriage, clash with the lack of clarity of existing regulations. Referring to the Marriage Law Number 1 of 1974, it does not explain in detail the concept of interfaith marriage, the Law only contains mixed marriages (citizenship). The research method is a qualitative research that uses normative juridical research methods. Qualitative research also includes the methodology used for research procedures that produce descriptive data. Descriptive data is data that is written using words in detail. In this study, the researcher also used a normative juridical approach. The technique used to collect data was by researching library materials. The data obtained from library research, which will then be arranged systematically and will be processed by qualitative descriptive analysis which will then be given conclusions from the data that has been analyzed. In this study, researchers are looking for answers to the main problems that have been formulated, namely: First, how is the legal status of interfaith marriages, secondly how is the regulation of interfaith marriage registration and thirdly how is interfaith marriage registration and its relation to population registration in Indonesia. The study resulted in the conclusion that whether or not a marriage is valid depends on the religious law of the bride and groom, then regulations regarding the registration of interfaith marriages are regulated in Pasal 35 huruf A UU Adminduk, then regarding the requirements for registering interfaith marriages are the same as the requirements for registering marriages in general, only there is one additional requirement, namely that previously there must be a permit in the form of a decision from the district court regarding the interfaith marriage (according to Pasal 35 huruf a UU Adminduk). Then the permit legalizes interfaith marriages. Therefore, the marriage can then be registered with the Population and Civil Registration Service. Keywords: Interfaith Marriage, Registration of Interfaith Marriage, Validity of Interfaith Marriage.